2001
DOI: 10.1046/j.1524-475x.2001.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of acute and chronic wound fluids on urokinase‐type plasminogen activator, urokinase‐type plasminogen activator receptor, and tissue‐type plasminogen activator in cultured human keratinocytes and fibroblasts

Abstract: The effect of wound fluids collected from acute well-healing wounds and chronic nonhealing venous leg ulcers on the plasminogen activation system of keratinocyte and fibroblast cell cultures was studied in a simplified wound-healing model. Acute wound fluid was collected from donor sites of split skin grafts at different time points representing the progressive healing of the wound. Urokinase-type plasminogen activator, tissue-type plasminogen activator, urokinase-type plasminogen activator receptor, and plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…The effect of gene silencing in pAEC AA was more difficult to assess due to the already reduced rate of repair observed in these cells. Previous work performed in keratinocytes has established the association of PAI‐1 expression and leading wound edges [52–54] and, more recently, Marquerlot et al [13] have shown in alveolar epithelial cells that the availability of matrix‐bound‐PAI‐1 is required for efficient healing. Moreover, immediately after wounding, PAI‐1 was shown to be dramatically increased in the newly deposited matrix at the leading edge of wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of gene silencing in pAEC AA was more difficult to assess due to the already reduced rate of repair observed in these cells. Previous work performed in keratinocytes has established the association of PAI‐1 expression and leading wound edges [52–54] and, more recently, Marquerlot et al [13] have shown in alveolar epithelial cells that the availability of matrix‐bound‐PAI‐1 is required for efficient healing. Moreover, immediately after wounding, PAI‐1 was shown to be dramatically increased in the newly deposited matrix at the leading edge of wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The test limb is maintained dependent for between 2 and 5 hours and the fluid that collects under the film aspirated using a sterile needle and syringe. 32,33 The occlusion technique has been used to collect fluid from chronic wounds, but it has also been applied to acute wounds, such as at skin donor sites. A major disadvantage of this technique is the time required to accumulate sufficient wound fluid for analysis.…”
Section: Wound Fluid Samplingmentioning
confidence: 99%
“…Urokinase‐type plasminogen activator is expressed by gingival fibroblasts during wound healing and in periodontitis‐affected gingival tissues (8–10). It has been observed that altered production of urokinase‐type plasminogen activator may lead to aberrant wound repair or to the perpetuation of chronic inflammatory reactions in several diseases or conditions in which connective tissue remodeling plays a significant role (9,11,12). Therefore, factors regulating the production of urokinase‐type plasminogen activator may critically modulate the evolution of tissue repair and inflammation.…”
mentioning
confidence: 99%